Висунення кандидатури чеського володаря Пршемисла Отакара ІІ на німецький трон та його пасивна участь у виборчих перегонах 1256–1257 рр. - Ліхтей, І. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2019)
У статті простежуються перипетії, що точилися довкола висунення кандидатури чеського володаря Пршемисла Отакара ІІ на
німецький трон, та з’ясовується його роль у виборчих перегонах 1256–1257 років. Автор відзначає, що невдовзі після того, як 1253 р. Пршемисл Отакар ІІ успадкував владу в Чеському королівстві, зріс його авторитет
серед можновладних князів Священної Римської імперії. Деякі з них
перебували в опозиції до німецького короля Вільгельма Голландського й
вирішили висунути на трон чеського володаря. Однак той, орієнтуючись
на Папську курію, не скористався цією можливістю, а після смерті
Вільгельма Голландського вже ніхто не висував його кандидатуру.
А тому Пршемисл Отакар ІІ як курфюрст пасивно поставився до виборів
нового німецького правителя й за посередництвом послів та уповноважених осіб підтримав обох претендентів — і Річарда Корнуельского, і
Альфонса Х Мудрого. Їхнє обрання засвідчило, що у Священній Римській
імперії продовжився період безкоролів’я — interregnum, що було на руку
Пршемислові Отакарові ІІ. The article traces the twists and turns concerning the nomination of Czech
Sovereign Přemysl Otakar II for the German throne, and his role in the
election race of 1256–1257. In preparing this study, the author investigated
Annals and Chronicles, created in different regions of the Holy Roman Empire.
In the middle of the 13th century the Czech Kingdom gradually reached the
level of European states in all spheres of social and political life, its authority
and power increased. In view of favourable international context in Central
Europe and the successful economic development, Czech Sovereigns from the
Přemyslid dynasty have begun to play important roles on the international
scene. The status and authorities of the Prince-electors attest to the recognition
of their authority. They were provided with the rights to elect the German
kings, which usually became Emperors of the Holy Roman Empire.
The author notes that shortly after Přemysl Otakar II inherited the power
in the Czech Kingdom in 1253, his authority among the powerful rulers of the
Holy Roman Empire increased. Some of them were in opposition to the
German King William of Holland and decided to nominate the Czech ruler.
However, he, focusing on the Pontifical Curia, did not use that opportunity,
and after the death of William of Holland no longer anyone proposed to
nominate him. That is why Přemysl Otakar II, as the prince-elector, was
passive in the election of a new German ruler and through the mediation of
ambassadors and authorized persons supported both pretenders — Richard of
Cornwall and Alfonso X the Wise. Their election testified that the period
without the king — interregnum — continued in the Holy Roman Empire has
been to Přemysl Otakar II's benefit.